Vocational education and training for African development: a literature review. (1st October 2020) - McGrath, Simon; Ramsarup, Presha; Zeelen, Jacques; Wedekind, Volker; Allais, Stephanie; Lotz-Sisitka, Heila; Monk, David; Openjuru, George; Russon, Jo-Anna
ABSTRACT: The SDGs mark the clearest global acceptance yet that the previous approach to development was unsustainable. In VET, UNESCO has responded by developing a clear account of how a transformed VET must be part of a transformative approach to development. It argues that credible, comprehensive skills systems can be built that can support individuals, communities, and organisations to generate and maintain enhanced and just livelihood opportunities. However, the major current theoretical approaches to VET are not up to this challenge. In the context of Africa, we seek to address this problem through a presentation of literatures that contribute to the theorisation of this new vision. They agree that the world is not made up of atomised individuals guided by a "hidden hand". Rather, reality is heavily structured within political economies that have emerged out of contestations and compromises in specific historical and geographical spaces. Thus, labour markets and education and training systems have arisen, characterised by inequalities and exclusions. These specific forms profoundly influence individuals' and communities' views about the value of different forms of learning and working. However, they do not fully define what individuals dream, think and do. Rather, a transformed and transformative VET for Africa is possible.